Thursday

March 5, 2015

March 5, 2015

Posted by **Akash** on Friday, June 10, 2011 at 1:27am.

- Class 12th Calculus -
**Reiny**, Friday, June 10, 2011 at 8:01amThe simple dy/dx = e^x(-sinx) + e^xcosx

= e^x(cosx - sinx)

RS = √2(e^x)(cos(x+π/4)

= √2(e^x)(cosxcosπ/4 - sinxsinπ/4)

= √2(e^x)(cosx(1/√2 - sinx(1/√2)

= e^x (cosx - sinx)

= the dy/dx from above

**Answer this Question**

**Related Questions**

Class 12th : Calculus - If y = sqrt(x-1)+sqrt(x+1),prove that sqrt(x^2-1)dy/dx=...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...

Calculus - Find the derivative of cos(sqrt(e^(x^3)cos(x)) I got -sin(sqrt(e^(x^3...

Calculus - Please look at my work below: Solve the initial-value problem. y'' + ...

RESPONSE to PreCalc Question - h t t p : / / w w w . j i s k h a . c o m / d i s...

Calc II - For the following question, we need to find the length of the polar ...

Calculus grade 12 - solve for (<_ = less than or equal to / pie = pie sign...

Geometry - Find 2 cos(x/2) sin(x/2) when x = -π/6. I know that cos(x/2...

Calculus - solve this equation on the given interval expressing the solution for...